MEMBANGUN KEUNGGULAN KHAS PERUSAHAAN - Setiawan, Andi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2010)
This articleÂ  is a preliminary concept of a research on the company specific advantage. A study on sustainable competitive advantage is a study which attracts researchers on doing strategic mangemen and marketing management researchs, since its potency to explore how long term company performance can be produced and increased. Most studies focus on the advantage from the point view of company resources basic,Â  and onlyÂ  few of them explore competitive advantage of end user.Â  The concept of business strategy, recently, refers to what customerâs need, hope and feel, on the contrary,Â Â  the source of short term characteristic advantage only focuses on the result and options that are achieved in the certain time. While,Â  competitive strategic advantage, with long-term customerâs orientation,Â  focuses on the future goal and concentrates in the present and future result. The basic implementation and formula of strategy is a process and mechanism of how company achieves and maintains sustainable benefit